Formalización en construcción de viviendas y pago del impuesto predial en el distrito de Trujillo, período 2010 - 2017 - Bejarano Acevedo, Deysi Carolina (2018)
In the present document “Formalization in Housing Construction and Property Tax Payment in the district of Trujillo, period 2010 – 2017”, the analysis is made of the evolution of Formalization in Housing Construction, the Property Tax Payment, and the relationship, if any, between both variables during the mentioned period. The main objectjve of the investigation is to determine the relationship between the Formalization in the Construction of Housing and Payment of Property Tax in the district of Trujillo, in the period between 2010 and 2017. To contrast the hypothesis formulated – there is a relationship and it is positive, between the Formalization in Housing Construction and Property Tax Payment in the district of Trujillo, period 2010 – 2017, an econometric model of Error Correction and the Cointegration Test was elaborated, using monthly data of Building Construction Licenses and income of Property Tax obtained from the archives of the Provincial Municipality of Trujillo. As a control variable, data from the regional GDP of La Libertad were used. The investigation shows that the evolution of the Formalization in Construction of Houses in the district of Trujillo, period 2010 – 2017, has high volatility; while the evolution of Property Tax Payment in the district of Trujillo shows an increasing trend during all the years of the study. It is also observed that there is a relationship between the Formalization in Housing Construction and the Property Tax Payment in the district of Trujillo, during the period 2010 – 2017 and this is positive; so for every 1% increase in Formalization in Housing Construction, the Property Tax Payment increases by 0.45%.